Analisis Penerapan Sistem Informasi Akuntansi Pelayanan Jasa Rawat Inap Dalam Menunjang Efektivitas Pengendalian Internal Pendapatan Rumah Sakit (Studi Kasus Rumah Sakit Mata Smec Medan) - Khairul Rahman; Kamilah Kamilah; Muhammad Lathief Ilhamy Nst (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This research aims to determine the application of the Inpatient Services Accounting Information System in Supporting the Effectiveness of Internal Control of Hospital Revenue at the SMEC Medan Eye Hospital. The method used in this research is qualitative with descriptive analysis, with data collection techniques through interviews, observation and documentation. The results of this research are that the implementation of the Inpatient Services Accounting Information System has run smoothly, effectively and efficiently. SMEC Medan Eye Hospital has used a computerized system in all areas of its activities. Starting from patient reception to cash receipts. The use of a computerized system is followed by an application, namely SIM RS, to simplify all operational activities. And has a role in supporting internal control of Hospital revenue. This is proven by the faster data entry and payment processes at the cashier. This is supported by an adequate accounting information system and is proven by the system running well and smoothly.